If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -84 = 7(8x + 4) Reorder the terms: -84 = 7(4 + 8x) -84 = (4 * 7 + 8x * 7) -84 = (28 + 56x) Solving -84 = 28 + 56x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56x' to each side of the equation. -84 + -56x = 28 + 56x + -56x Combine like terms: 56x + -56x = 0 -84 + -56x = 28 + 0 -84 + -56x = 28 Add '84' to each side of the equation. -84 + 84 + -56x = 28 + 84 Combine like terms: -84 + 84 = 0 0 + -56x = 28 + 84 -56x = 28 + 84 Combine like terms: 28 + 84 = 112 -56x = 112 Divide each side by '-56'. x = -2 Simplifying x = -2
| n/6+7=10 | | -1.5-7.1x=-4.58-9.9x | | 2x+18+36=180 | | 4x+44y=-28 | | 2x+18+36=90 | | n/3-5=7 | | (1/2)x-3=(3/2)x+4 | | 2(x+3)+12=8 | | 5a+2(2a+2)=7a-24 | | -9+89x+10x^2=0 | | 7x+3x=5x+13 | | -14=3x+7 | | 8h=288 | | 6(2x-7)=12x-17 | | 2x+17=x+97 | | -4(x-4)+2(6x-4)=4x+8x | | 4y-19=-25+2y | | 2x-10=8x | | 6t-16+t^2= | | (x-11)-5=-5 | | 20x-15=20+9x | | -3x+6(x+4)=9x | | x-0.8=9.96 | | .5X+.5X=.5+1 | | 37=18p+1 | | 14-23=-3x | | 16-2B-5+8n=65 | | 10(5+S)=130 | | -5x-3=42 | | 1809=2.1x | | -4.6=3.4-4y | | -9(6+n)-2n=-10 |